Papal Primacy and Infallibility in the Context of Synodality - Neuner, Peter (Asian Horizons, 2020)
150 years ago, Vatican I council defined the dogmas on papal primacy and infallibility. The hierarchy was frightened by the massacres of the French Revolution, a widespread anti-Catholic hostility and an atheist philosophy. The Popes were convinced, that Luther’s ideas of freedom and autonomy had caused these disasters. Thus, they strived to reinforce authority and obedience and so they prepared the way for a rather absolutistic regime of the Church. Vatican II council had a different approach. Following the leitmotif of aggiornamento, it opened the Church to the aspirations of people and to the signs of the time. Nevertheless, it quoted the dogmas of 1870 and these even reappeared in the Codex 1983. This article proposes a rereading of Vatican I in the light of Vatican II, which might overcome an absolutistic approach and open the Church to synodality and ecumenism.